Implementasi Metode Design Thinking pada Sistem Bank Sampah Kelurahan Brumbungan Kota Semarang - Rizqi Setyawan, Raffly; Eka Ardhianto (JITU, 2025)
Waste banks are one of the community-based waste management solutions that continue to grow, as implemented by the "Sampahku Berkahmu" waste bank in Kelurahan Brumbungan. However, in practice, several challenges still exist, particularly in the manual recording and reporting systems. With the advancement of digital technology, there is a need for a digital application that can simplify the management process of waste banks more efficiently and accommodate the limited technological literacy among the managers. This study aims to design a simple and user-friendly waste bank application that can assist both managers and users in monitoring and managing transaction data and waste weighing reports. The method used in this study is Design Thinking, which consists of five stages: empathize, define, ideate, prototype, and test. Data was collected through interviews and observations of the managers and users of the waste bank in Kelurahan Brumbungan. The application was developed using the Kodular platform and evaluated using the System Usability Scale (SUS) to measure its usability. The test results showed a SUS score of 85, which falls under the “Excellent” category and is classified as grade B, indicating that the application was well-received by users and can serve as an effective digital solution for waste bank data management.